2004
DOI: 10.1890/1540-9295(2004)002[0403:ahescb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Avian habitat evaluation: should counting birds count?

Abstract: There are times when birds reproduce at higher rates in places where they are less abundant, limiting the generally accepted value of bird counts as environmental indicators. But how often, and under what circumstances, does this happen? In 109 published cases involving 67 species across North America and Europe, higher density sites displayed greater recruitment per capita and per unit of land area in 72% and 85% of cases, respectively. The frequency of negative relationships between abundance and reproductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
119
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(126 citation statements)
references
References 30 publications
2
119
3
Order By: Relevance
“…This pattern, obtained at a very broad spatial scale, is relevant for large-sized bird species for which only low population densities in their preferred habitats can be expected (Carrascal & Tellería, 1991), because population density is usually the only ecological parameter that can be feasibly studied over large areas to define protection priorities and to carry out environmental assessment (Brawn and Robinson 1996;Vickery et al 1992). This result is not consistent with Van Horne's (1983) concern about animal abundance as a misleading indicator of environmental quality, but agrees with the review by Bock and Zach (2004) showing that birds in Northern Hemisphere are usually more abundant in habitats where per capita reproduction is highest, regardless of the type of bird or habitat, degree of territoriality and migratory status. Nevertheless, human impact may hamper the ability of birds to recognize and occupy the best suited places for reproduction, decreasing the intensity of relationship between population density and breeding success (Bock and Zach 2004).…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…This pattern, obtained at a very broad spatial scale, is relevant for large-sized bird species for which only low population densities in their preferred habitats can be expected (Carrascal & Tellería, 1991), because population density is usually the only ecological parameter that can be feasibly studied over large areas to define protection priorities and to carry out environmental assessment (Brawn and Robinson 1996;Vickery et al 1992). This result is not consistent with Van Horne's (1983) concern about animal abundance as a misleading indicator of environmental quality, but agrees with the review by Bock and Zach (2004) showing that birds in Northern Hemisphere are usually more abundant in habitats where per capita reproduction is highest, regardless of the type of bird or habitat, degree of territoriality and migratory status. Nevertheless, human impact may hamper the ability of birds to recognize and occupy the best suited places for reproduction, decreasing the intensity of relationship between population density and breeding success (Bock and Zach 2004).…”
Section: Discussioncontrasting
confidence: 66%
“…This result is not consistent with Van Horne's (1983) concern about animal abundance as a misleading indicator of environmental quality, but agrees with the review by Bock and Zach (2004) showing that birds in Northern Hemisphere are usually more abundant in habitats where per capita reproduction is highest, regardless of the type of bird or habitat, degree of territoriality and migratory status. Nevertheless, human impact may hamper the ability of birds to recognize and occupy the best suited places for reproduction, decreasing the intensity of relationship between population density and breeding success (Bock and Zach 2004). This seems not to be the case for Bonelli's eagle in Spain, because the younger reproductive individuals (less than 4 years of age) usually nest in less favourable areas (closer to roads and urban areas than adults; Penteriani et al 2003), and several authors have described that the Bonelli's eagle occupies areas of high human density in man-made environments (Gil-Sánchez et al 1994;López-López et al 2004).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Although density is generally a good predictor of reproductive success (Bock & Jones 2004), higher quality habitat does not always equal greater density, and likewise, greater density does not necessarily equal higher quality habitat. Density and habitat quality can be decoupled by at least (1) territoriality and other social interactions, (2) Tab.…”
Section: Discussionmentioning
confidence: 99%
“…Our forest clearing experiment showed that roseate tern individuals breeding under a certain forest canopy cover readily moved to a forest clearing in the year following its formation. As nest density is often correlated with habitat quality (Bock & Jones 2004), this suggests that forest clearings were of higher quality to breeding roseate terns than closed canopy areas.…”
Section: Spatial Distribution Of Nesting Ternsmentioning
confidence: 99%